Steroid-Responsive Post-Traumatic Persistent Neutrophilic Meningitis - Mahboubeh Haddad; Fereshte Sheybani; Nahid Olfati; Yeganeh Azhdari (Case Reports in Medicine)
Post-traumatic meningitis is a potentially fatal condition that presents as a diagnostic and therapeutic challenge. The vast majority of post-traumatic meningitides are caused by infectious pathogens, most commonly multi-drug-resistant (MDR) bacterial pathogens. However, aseptic meningitis occurs less frequently due to tissue response to injury or stimulation by noninfectious agents, such as blood breakdown products or chemicals. Here, we present a case of post-traumatic persistent neutrophilic meningitis who was found to be steroid responsive. Diagnostic evaluation in our patient did not reveal any infectious pathogen, and the patient did not respond to broad-spectrum antimicrobial treatment. We suggest that physicians who treat patients with post-traumatic meningitis should consider steroid-responsive post-traumatic persistent neutrophilic meningitis (SPNM) in the list of differential diagnosis particularly when no infectious etiology is found and the patient does not respond to empirical antimicrobial treatment. Brain injury-induced immune dysregulation causing exaggerated inflammatory reaction might play a role in the pathogenesis of SPNM; however, further neuropathological studies are absolutely necessary to evaluate and characterize trauma-induced immune dysregulation.